Cost-effectiveness and quality of life in surgeon versus general practitioner-organised colon cancer surveillance: a randomised controlled trial. Issue 4 (4th April 2013) - Augestad, Knut Magne; Norum, Jan; Dehof, Stefan; Aspevik, Ranveig; Ringberg, Unni; Nestvold, Torunn; Vonen, Barthold; Skrøvseth, Stein Olav; Lindsetmo, Rolv-Ole
Abstract : Objective: To assess whether colon cancer follow-up can be organised by general practitioners (GPs) without a decline in the patient's quality of life (QoL) and increase in cost or time to cancer diagnoses, compared to hospital follow-up. Design: Randomised controlled trial. Setting: Northern Norway Health Authority Trust, 4 trusts, 11 hospitals and 88 local communities. Participants: Patients surgically treated for colon cancer, hospital surgeons and community GPs. Intervention: 24-month follow-up according to national guidelines at the community GP office. To ensure a high follow-up guideline adherence, a decision support tool for patients and GPs were used. Main outcome measures: Primary outcomes were QoL, measured by the global health scales of the European Organisation for Research and Treatment of Cancer QoL Questionnaire (EORTC QLQ C-30) and EuroQol-5D (EQ-5D). Secondary outcomes were cost-effectiveness and time to cancer diagnoses. Results: 110 patients were randomised to intervention (n=55) or control (n=55), and followed by 78 GPs (942 follow-up months) and 70 surgeons (942 follow-up months), respectively. Compared to baseline, there was a significant improvement in postoperative QoL (p=0.003), but no differences between groups were revealed (mean difference at 1, 3, 6, 9, 12, 15, 18, 21 and 24-month follow-up appointments): Global Health; Δ−2.23, p=0.20; EQ-5D index; Δ−0.10, p=0.48, EQ-5D VAS; Δ−1.1, p=0.44. There were no differences in time to recurrent cancer diagnosis (GP 35 days vs surgeon 45 days, p=0.46); 14 recurrences were detected (GP 6 vs surgeon 8) and 7 metastases surgeries performed (GP 3 vs surgeon 4). The follow-up programme initiated 1186 healthcare contacts (GP 678 vs surgeon 508), 1105 diagnostic tests (GP 592 vs surgeon 513) and 778 hospital travels (GP 250 vs surgeon 528). GP organised follow-up was associated with societal cost savings (£8233 vs £9889, p<0.001). Conclusions: GP-organised follow-up was associated with no decline in QoL, no increase in time to recurrent cancer diagnosis and cost savings. Trial registration: ClinicalTrials.gov identifier NCT00572143 .